Trauma or Drama: A Predictive Processing Perspective on the Continuum of Stress - Krupnik, Valery (Frontiers in Psychology, 2020)
The notion of trauma has been liberally used both in clinical literature and general discourse. However, no consensus exists on its exact meaning and definition. Whereas traditionally trauma has been mostly associated with criterion A of acute and post-traumatic stress disorders as defined in the Diagnostic and Statistical Manual of Mental Disorders, many researchers find this definition too constraining and not accounting for the complexity and many aspects of psychological trauma. This touched off a quest for a broader more accommodating trauma concept, and a dimensional view of trauma has been suggested with PTSD as its extreme manifestation. The dimensional view also has its detractors arguing that a “conceptual bracket creep” may undermine the category’s utility. Both categorical and dimensional views mostly rely on trauma’s clinical phenomenology and lack a unified theoretical basis. In an attempt to reconcile this contradiction, a hybrid categorical-dimensional model of trauma based on the general theory of stress has been recently proposed (Krupnik, 2019). In this report, we explore the categorical boundary of the trauma concept, as posited by the model, within the predictive processing framework (PPF). We integrate the PPF view with the theory of stress. In conclusion, we briefly discuss how the proposed model of trauma may guide clinical practice.